The Efficacy of Intradermal Injection of Botulinum Toxin in Patients with Post-Herpetic Neuralgia - Emad, M R (Kowsar, 2011)
BACKGROUND: Several treatments have been suggested in shingles viral infection caused by Varicella zoster virus that may lead to complications such as PHN (Post-herpetic neuralgia). Intradermal injection of botulinum toxin was shown with few side effects. This study evaluates the efficacy of intradermal injection of botulinum toxin in patients suffering from PHN. METHODS: Fifteen patients suffering from PHN for more than1 month were enrolled. Data collected were patients' age, sex, and lesion site, the dermatome involved and the duration and severity of pain by visual analog scale (VAS). Botulinum (15 units /every 10 cm(2) of body involved) was injected intradermally. The patients were followed 2, 14 and 30 days after injection. RESULTS: Of participants, 6 were males and 9 females. The mean age was 60 years and the mean duration of neuralgia was 6.5 months. The mean VAS on day 2 was 6.4, on day 14 was 7.2 and after 30 days was 7.6. The overall pain after injection decreased but was not significant. CONCLUSION: It seems that intradermal injection of botulinum toxin decreases pain in PHN patients and this decrease is less prominent by passing time.